Factors Affecting Capital Budgeting Decisions: A Structural Equation Modeling Study - Gupta, Divya; Mohanty, R. P. (Indian Journal of Finance, 2012)
The purpose of this paper is to validate the impact of various factors which influence the capital budgeting decisions taken by firms. Capital budgeting decisions use the structural equation modeling approach after undergoing factor analysis, which results in a better developed model after various rotations with different variables for arriving at the best fit structural model. This paper is based on primary data. Using a sample size of 75 companies, and by categorizing the variables into four factors - Size, Risk, Social Cost Benefit Analysis (SCBA) and Trait, a regression analysis was conducted, which found that the first three factors (Size, Risk and SCBA) are significant and influence the decision of acceptance of the Type of Capital Budgeting Technique (TCBT) used by the companies.